Experimental investigation of small radial-flow expander in micro-scale organic rankine cycle powered by low temperature heat source - Tongchana Thongtip; Wichean Singmai; Suparat Jamsawang; Natthawut Ruangtrakoon; Kittiwoot Sutthivirode (Energy Conversion and Management X, 2025)
• The development and performance investigation of the radial-flow expander is proposed. • Performance under various working conditions is studied experimentally. • The thermal efficiency of up to 3.58% and isentropic efficiency of up to 74% • The developed expander shows the potential for practical use of a micro-scale ORC. The in-house development of a radial-flow expander is proposed which aims to investigate the performance under various working conditions. The radial-flow expander is installed into a micro-scale Organic Rankine Cycle (ORC) test bench. An experimental investigation is also proposed in an attempt to discuss the operating characteristics and the system performance. The mathematical model for designing the expander is proposed and the validations of the designed performance parameters with the tested parameters is also implemented to ensure that the radial-flow expander is developed correctly. The operating characteristics of the vapour-generator with variations in the working fluid flow rate which reflects the best heat transfer performance is also a main focus. This is significant for producing the thermodynamic state of the vapour at the outlet of the vapour-generator. The overall heat transfer coefficient (U ref ) based on the flow boiling at the vapour-generator is determined. The maximum shaft power and maximum thermal efficiency are determined under various working conditions. This paper also provides evidence of the ORC system operating with a low temperature heat source (range 80–90 °C). The thermal efficiency is as high as 2.5–3.5 % depending on the the working conditions. The overall heat transfer coefficient for the flow boiling at the vapour generator is 280 to 700 W/m 2 .K.
Keywords: Thermodynamic and Exergetic Analyses of Power and Cooling Systems; Heat Transfer and Optimization; Advanced Thermodynamics and Statistical Mechanics